Analisis Pembentukan Nilai & Karakter Anak dalam Aspek Kemandirian dan Religius di SD Muhammadiyah Kriyan - Achmad Nazarudin; Aan Widiyono (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research is based on cases related to children in Indonesia. Various cases of KTA (cases related to children) are a portrait of how good values ​​and character have not been rooted in some children in the current generation. Various case findings related to children are dominated by cases related to religion in the form of religious attitudes, and the emergence of the strawberry generation in children today. There are many factors that influence the occurrence of cases related to children, including family, environment and school. One effort to overcome cases related to children is through school culture, school is one of the most influential environments in shaping children's personality traits. This research aims to determine the implementation of school culture as a character education process, especially independent character and religious attitudes in children. This research uses descriptive qualitative research. Research data was collected through observation, interviews and documentation techniques. The subjects in this research were all students, teaching staff at Muhammadiyah Kriyan Elementary School. The results of the research show that through the implementation of school culture it can be used as a means in the process of forming children's character, the form of school culture that takes place at Muhammadiyah Kriyan Elementary School is in the form of Morning Activities and MDES (Muhammadiyah Boarding Elementary School). The positive impact in the implementation of school culture has been felt by the existence of several positive attitudes exemplified by students, so it can be concluded from several findings of attitudes highlighted by students, school culture at Muhammadiyah Kriyan Elementary School can be used as a school tool in efforts to shape children's character at the elementary school level.